SEO: A unique approach to enhance the site rank by implementing Efficient Keywords Scheme - Rehman, Khalil ur; Yasin, Anaa; Mahmood, Tariq; Azeem, Muhammad; Ali, Saqib (PeerJ Preprints, 2019)
In search engine optimization individual website pages are optimized through precise keywords, while the websites are optimized using back link watch. The existing literature has no proper guideline for keywords selection and back link generation. In this research, we proposed a model for making back link watch generation and the selection of keywords through precise research analysis. The information on webpages consist of specific keywords while the website traffic is monitored through referrals. we concluded that during the development of Page Content, and architecture, if selected keywords are used in Title, Headings and Meta Tag then the page result is higher in search results. Moreover, for the back-link generation use a shorter volume of URL that monitor the complete traffic of a site can be placed on trusted location which increase the ranks of a site. Proposed model has been validated by comparing quantitative data of website rank taken before and after implementation of framework. Results revealed that overall increase gained in site rank by applying the proposed model was 40%.
Keywords: On-site Optimization; Off-site Optimization; Site Traffic; Link Generation; Keywords Competitor Analysis; SEO; Website Crawling; URL Analysis